Insight to the residue in P2 position prevents the peptide inhibitor from being hydrolyzed by serine proteases. Issue 6 (2nd June 2020) - Xue, Guangpu; Xie, Xie; Zhou, Yang; Yuan, Cai; Huang, Mingdong; Jiang, Longguang
ABSTRACT: Peptidic inhibitors of proteases are attracting increasing interest not only as drug candidates but also for studying the function and regulation mechanisms of these enzymes. Previously, we screened out a cyclic peptide inhibitor of human uPA and found that Ala substitution of P2 residue turns upain-1 to a substrate. To further investigate the effect of P2 residue on the peptide behavior transformation, we constructed upain-1-W3F, which has Phe replacement in the P2 position. We determined K D and Ki of upain-1-W3F and found that upain-1-W3F might still exist as an inhibitor. Furthermore, the high-resolution crystal structure of upain-1-W3F·uPA reveals that upain-1-W3F indeed stays as an intact inhibitor bind to uPA. We thus propose that the P2 residue plays a nonnegligible role in the conversion of upain-1 to a substrate. These results also proposed a strategy to optimize the pharmacological properties of peptide-based drug candidates by hydrophobicity and steric hindrance. Abbreviations : uPA: urokinase-type plasminogen activator; SPD: serine protease domain; S1 pocket: specific substrate-binding pocket Graphical abstract: : Crystal structure of upain-1-W3F·uPA suggests P2 residue of upain-1 series as a key factor in the conversion of upain-1 to a slow substrate.